2009
DOI: 10.1007/s12562-009-0116-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of recooking on volatile and non-volatile compounds found in silver carp Hypophthalmichthys molitrix

Abstract: Volatile and non-volatile compounds, which contribute to flavor in raw fish, were compared in raw, cooked and recooked silver carp. In total, 20, 34 and 34 volatile compounds, including aldehydes, alcohols, ketones, hydrocarbons and heterocyclic compounds, were identified in raw, cooked and recooked samples, respectively. Cooking the samples resulted in a significant increase in volatile compounds and the formation of new aldehydes, alcohols, ketones, hydrocarbons and heterocyclic compounds. In addition, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
1
10

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 42 publications
1
48
1
10
Order By: Relevance
“…A higher number of volatile compounds derived from lipid oxidation was detected in cooked yellowtail, both DM and OM, than in the raw samples used in our previous study [4]. Liu et al demonstrated that the cooking raw silver carp resulted in a significant increase in volatile compounds and the formation of new aldehydes, alcohols, ketones, hydrocarbons, and heterocyclic compounds [2]. Moreira et al also reported cooking enhanced the production/liberation of volatile compounds of Senegalese sole [6].…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…A higher number of volatile compounds derived from lipid oxidation was detected in cooked yellowtail, both DM and OM, than in the raw samples used in our previous study [4]. Liu et al demonstrated that the cooking raw silver carp resulted in a significant increase in volatile compounds and the formation of new aldehydes, alcohols, ketones, hydrocarbons, and heterocyclic compounds [2]. Moreira et al also reported cooking enhanced the production/liberation of volatile compounds of Senegalese sole [6].…”
Section: Discussionmentioning
confidence: 56%
“…These results suggest that the reheating after storage led to an increment in the intensity of the unpleasant odor of cooked fish, and that DM made a large contribution to the deterioration of its odor. Liu et al reported that silver carp reheated after 24 h of storage at 4 °C showed a significant decrease in volatile compounds [2]. However, WOF develops rapidly in refrigerated meats, including poultry, and volatile compounds derived from lipid oxidation, such as hexanal, are associated with the development of off-odor [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, it must be noticed that histidine was detected as the main free amino acid in silver carp fillet (Liu et al . ). Because of the decarboxylation of this amino acid, it seems that this fish makes major histamine‐related health problems in fish industry during storage.…”
Section: Introductionmentioning
confidence: 97%